2021
DOI: 10.1109/access.2021.3083804
|View full text |Cite
|
Sign up to set email alerts
|

A Health Data Map-Based Ensemble of Deep Domain Adaptation Under Inhomogeneous Operating Conditions for Fault Diagnosis of a Planetary Gearbox

Abstract: A deep learning model trained under a specific operating condition of the gearbox often experiences an overfitting problem, which makes it impossible to diagnose faults under different operating conditions. To solve this problem, this paper proposes an ensemble of deep domain adaptation approaches with a health data map. As a fundamental approach to alleviate the domain shift problem due to inhomogeneous operating conditions, the vibration signal is transformed into an image-like simplified health data map tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…HDMap can visualize vibration signals in a more intuitive manner by considering modulation characteristics caused by the revolving planet gears, which allows for the independent interpretation of fault signatures from the gears. Subsequent validation studies have demonstrated that HDMap can outperform time, frequency, and time-frequency domain signals when used as input to the deep learning-based fault diagnosis model of the planetary gearbox [11]. However, a previous study has shown that HDMap still requires further domain adaptation to solve the remaining domain shift problem when the domain gap is significant.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…HDMap can visualize vibration signals in a more intuitive manner by considering modulation characteristics caused by the revolving planet gears, which allows for the independent interpretation of fault signatures from the gears. Subsequent validation studies have demonstrated that HDMap can outperform time, frequency, and time-frequency domain signals when used as input to the deep learning-based fault diagnosis model of the planetary gearbox [11]. However, a previous study has shown that HDMap still requires further domain adaptation to solve the remaining domain shift problem when the domain gap is significant.…”
Section: Related Workmentioning
confidence: 99%
“…One such physics-guided signal representation approach for gearbox health monitoring is health data map (HDMap) that has recently been introduced [10]. It has been shown that HDMap can enhance the performance of DL-based fault diagnosis methods compared to raw input signals [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ha and Youn, 2021 126 performed fault diagnosis of planetary gearbox with the use of CNN and maximum classifier discrepency (MCD). In this study, vibration signals were first converted into image map using time syncronous averaging (TSA) which visualizes the fault toothwise.…”
Section: Based Rotating Machines Fault Diagnosismentioning
confidence: 99%
“…Although traditional machine learning methods such as SVM have good performance on small sample datasets, these methods require a lot of expertise and domain knowledge, and the feature engineering steps need to be done manually. Since deep learning does not require manual feature extraction, deep learning has been applied to gear fault diagnosis by scholars [ 15 , 16 , 17 , 18 , 19 , 20 ]. Nguyen et al [ 21 ] used ANC and DNN to build a sensitive gear fault diagnosis model that can effectively and accurately diagnose the types of faults with different shaft speeds and have high classification accuracy.…”
Section: Introductionmentioning
confidence: 99%